2017
DOI: 10.1080/0075417x.2017.1323945
|View full text |Cite|
|
Sign up to set email alerts
|

Psychodynamic psychotherapy for children and adolescents: an updated narrative review of the evidence base

Abstract: Introduction Psychodynamic psychotherapy with children and adolescents is an approach to working with young people that draws on psychoanalytic ideas, whilst also integrating ideas from other disciplines, including developmental psychology, attachment theory and neuroscience (Alvarez, 2012; Kegerreis & Midgley, 2014; Lanyardo & Horne, 2009). Although the term 'psychodynamic therapy' covers a range of approaches, most of them share what Kegerreis & Midgley (2014) refer to as "the central idea ... that behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 47 publications
1
56
0
5
Order By: Relevance
“…Psychodynamic therapy, which works with insight into conflicts and focuses on problems and stress in close relationships, is particularly suitable for these patients. In fact, psychodynamic therapy in adolescents has historically a long tradition (Freud, 1958) and is offered frequently (Midgley et al, 2017). Looking at research, however, it is surprising that there are only a limited number of studies that assess the efficacy of psychodynamic therapy in this age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychodynamic therapy, which works with insight into conflicts and focuses on problems and stress in close relationships, is particularly suitable for these patients. In fact, psychodynamic therapy in adolescents has historically a long tradition (Freud, 1958) and is offered frequently (Midgley et al, 2017). Looking at research, however, it is surprising that there are only a limited number of studies that assess the efficacy of psychodynamic therapy in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reviews on the state of research still indicate a high demand for psychodynamic psychotherapy studies (Midgley & Kennedy, 2011;Midgley et al, 2017). The recent meta-analysis by Weisz et al (2017) summarizes 50 years of research in this area and includes 447 studies and 30,031 patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study was designed to develop Brazilian psychodynamic psychotherapy (PDT) and cognitivebehavioral therapy (CBT) prototypes for children with internalizing disorders (ID) and externalizing disorders (ED). Over the last few years, an increasing body of evidence has been accumulating for the effectiveness of PDT and CBT for children with different symptoms, 1,2 reinforcing the relevance of these treatments. However, studies that focus on how psychotherapies promote change are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Research on child and adolescent psychodynamic psychotherapy (PP) has made significant advances. Many studies have already demonstrated the effectiveness of this model of treatment and have demonstrated that the effects exceed those of maturation and spontaneous remission (Midgley et al ., ; Midgley & Kennedy, ; Palmer, Nascimento & Fonagy, ). However, the question arises as to what aspects of the treatment lead to the effectiveness of this theoretical model (Ablon, Levy & Katzenstein, ).…”
mentioning
confidence: 99%
“…However, the question arises as to what aspects of the treatment lead to the effectiveness of this theoretical model (Ablon, Levy & Katzenstein, ). Understanding why and how changes happen as a result of a therapeutic intervention might help to identify the active components or mechanisms of change that underlie successful clinical interventions (Midgley et al ., ; Midgley & Kennedy, ).…”
mentioning
confidence: 99%